Peran KSU Kota Santri dalam Meningkatkan Kesejahteraan Masyarakat - Janah, Miftahul; Nurwanti, Nurwanti; Utami, Duwi; Adinugraha, Hendri Hermawan (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2022)
The existence of the Multipurpose Cooperative "Santri City" has the role of an economic system that has business opportunities to create a community that still lacks in meeting their needs. This cooperative as a forum for conducting business activities certainly has a role to improve the economy of the community in the surrounding area. The purpose of this study was to determine the role of KSU "Santri City" in improving the welfare of the community in Kajen District, Pekalongan Regency. The research method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. Determination of informants is done by using a purposive technique on the cooperative management. Based on the results of this study, it shows that this cooperative is able to improve the welfare of its members by carrying out various credits in various forms, namely money, electronics and vehicles. And this cooperative has a role to provide business capital to its members.